An ALMA/HST study of millimeter dust emission and star clusters - Turner, Jordan A.; Dale, D. A.; Adamo, A.; Calzetti, D.; Grasha, K.; Grebel, Eva K.; Johnson, K. E.; Lee, J. C.; Smith, L. J.; Yoon, I. (The astrophysical journal, 2019)
We present results from a joint ALMA/HST study of the nearby spiral galaxy NGC 628. We combine the Hubble Space Telescope (HST) Legacy ExtraGalactic UV Survey (LEGUS) database of over 1000 stellar clusters in NGC 628 with ALMA Cycle 4 mm/submillimeter observations of the cold dust continuum that span ˜15 kpc2 including the nuclear region and western portions of the galaxy’s disk. The - resolution—1.″1 or approximately 50 pc at the distance of - NGC 628—allows us to constrain the spatial variations in the slope of the millimeter dust continuum as a function of the ages and masses of the nearby stellar clusters. Our results indicate an excess of dust emission in the millimeter, assuming a typical cold dust model for a normal star-forming galaxy, but little correlation of the dust continuum slope with stellar cluster age or mass. For the depth and spatial coverage of these observations, we cannot substantiate the - millimeter/submillimeter excess arising from the processing of dust grains by the local interstellar radiation field. We detect a bright unknown source in NGC 628 in ALMA bands 4 and 7 with no counterparts at other wavelengths from ancillary data. We speculate this is possibly a dust-obscured supernova.
Gesehen am 06.03.2020